Market conjuncture and microeconomic aspects of innovation management - V.L. Smiesova; N.S. Kovtun (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The article has substantiated that innovation activity is primarily identified with the activities of enterprises and organizations, so the study of this problem at the micro-level is important and relevant. It was emphasized that clarification of the essence of innovation activity and the main functions of managing this activity at the micro-level, the impact of innovation activity on expanding the boundaries of production possibilities is an urgent task in the process of finding the most effective ways of development in the long term. The purpose of the article is to substantiate the essence of the innovation activity of enterprises (firms), clarify the essence of innovation management at the micro-level, determine the functions of innovation management, as well as the impact of innovation on expanding the boundaries of production possibilities. The article has analyzed the views of foreign scientists on the essence and role of innovation in the economy. The main definitions of the concept of "innovative activity", proposed by scientists-economists, international organizations and used in the legislation of Ukraine, has been considered. The weaknesses and advantages of these definitions has been substantiated. The author's definition of the concept of "innovative activity" has been proposed. The influence of innovation activity of micro-level subjects on the expansion of the boundaries of production possibilities, economic growth and economic development both at the level of each individual enterprise (firm) and at the level of the whole society has been revealed. The interrelation between the management of innovation activity and enterprise income, competitiveness and long-term development has been revealed. The author's definition of the concept of "management of innovation activity" has been formulated. They also defined the main functions of innovation activity management: planning, organization, control, stimulation, forecasting. The characteristics of these functions at the micro-level has been formulated. The need for the formation of effective tools and mechanisms for managing innovation activities at the micro-level has been emphasized.